Challenges of caring for transgender and gender diverse patients with rheumatic disease: presentation of seven patients and review of the literature. Issue 2 (5th March 2023) - Mathias, Kristen; Mathias, Lauren; Amarnani, Abhimanyu; Samko, Tracey; Lahita, Robert G.; Panush, Richard S.
Abstract : Purpose of review: As perspectives on sex and gender identity have evolved, there has been an increase in the practice of transgender medicine. Within rheumatology, however, there is a dearth of information about rheumatic disease in transgender and gender diverse (TGGD) individuals. This is important, as sex hormones affect the etiopathogenesis and expression of autoimmune diseases. We therefore sought to identify TGGD patients with rheumatic disease, review their clinical courses, and appraise existing literature about this population. Recent findings: Of 1053 patients seen at the Los Angeles County and University of Southern California Medical Center from 2019 through 2021, five transgender men and two transgender women with rheumatic disease were identified. Most patients' disease courses were not overtly impacted by gender affirming hormone therapy (GAHT). Six of seven patients had psychosocial barriers to care. Our systematic review found 11 studies with 11 transgender women and two transgender men. In 12 of 13 patients, GAHT possibly modulated the patients' rheumatic disease. Summary: Our observations suggest GAHT need not be a strict contraindication in TGGD patients with rheumatic disease. TGGD patients often face significant psychosocial barriers. Additional information about this population and empathy toward their health disparities are needed.